Application of occlusal indices in orthodontic practice - Đorđević Jelena; Šćepan Ivana; Glišić Branislav (Serbian Medical Society - Dental Section, Belgrade, 2009)
Introduction. Occlusal indices were designed to improve diagnostic criteria and to enable an objective assessment of malocclusion severity. The aim of this study was to present the most frequently used occlusal indices in orthodontic practice and to determine their reliability when applied to dental models. Material and Methods. Three occlusal indices were selected for analysis: the Index of Orthodontic Treatment Need (IOTN), the Peer Assessment Rating Index (PAR) and the Index of Complexity, Outcome and Need (ICON). Twenty dental models of patients referred to Department of Orthodontics, School of Dentistry, Belgrade, with malocclusions of different type and severity were used in this study. All dental models were measured by three afore mentioned indices twice, two months apart, in order to determine intraexaminer reliability. Results. The results showed that three indices had good reliability. Weighted Kappa was calculated for IOTN (0.72 and 0.79 for the aesthetic and the dental health component, respectively) and root mean square error was calculated for PAR and ICON (2.1 and 4.5, respectively). There was no statistically significant difference in scores between two measurements of these two indices (p<0.01). Conclusion. Application of occlusal indices enables orthodontists to determine priorities in patient care, planning of orthodontic service, monitoring and promotion of standards. Occlusal indices are reliable diagnostic criteria.